Programmed Cell Death, Proliferating Cell Nuclear Antigen and p53 Expression in Mouse Colon Mucosa during Diet-Induced Tumorigenesis - Mauro Risio; Ivana Sarotto; Francesco Paolo Rossini; Harold Newmark; Kan Yang; Martin Lipkin (Analytical Cellular Pathology)
Western‐style diets (WDs) trigger and sustain the early phases of tumorigenesis in mouse colon, and when continued throughout the life span lead to the development of dysplastic crypts. In order to evaluate the roles both of cell proliferation and programmed cell death (PCD) in WD‐induced tumorigenesis, immunohistochemical detection of proliferating nuclear antigen (PCNA), in situ end labeling (TUNEL) of DNA breaks, and p53 protein were carried out in mouse colonic mucosa during prolonged feeding of two WDs. PCNA Labeling Index of colonic crypts was significantly higher in WD‐treated animals than in controls only at the beginning of the nutritional study, the gap rapidly bridged by increased cell proliferation spontaneously occurring in the colonic mucosa during aging. A transient early homeostatic activation of PCD at the base of the crypt also was observed in WD groups. No changes in PCD were seen in the upper third of the crypt or in surface epithelium throughout the study, indicating that PCD in that colonic crypt segment produces a constant flux of cell loss, uninfluenced by homeostatic fluctuations. A major finding was an irreversible, progressive, age‐related decline of PCD at the crypt base in both control and treated animals that occurred during the second half of the rodents  life span. p53 protein was not immunohistochemically detected, suggesting that neither overexpression of wild‐type nor mutated forms of the protein are involved in the above mentioned changes.